Himalayan wild cherry (Prunus cerasoides) as a new natural host of Cherry necrotic rusty mottle virus (CNRMV) and a possible role of insect vectors in their transmission. (6th January 2015) - Awasthi, P.; Ram, R.; Reddy, S.G.E.; Nadda, Gireesh; Zaidi, A.A.; Hallan, V.
Abstract A Himalayan wild cherry (Hwc) tree (Prunus cerasoides) growing in the vicinity of an already reported Cherry necrotic rusty mottle virus (CNRMV) infected bamboo (Dendrocalamus hamiltonii) showed severe virus‐like symptoms on the leaves consisting of marginal chlorosis, mosaic, shot holes and necrotic spots. Reverse transcription‐polymerase chain reaction (RT‐PCR) using virus specific primers confirmed the presence of the virus. In order to assess the prevalence of this virus, 40 symptomatic and asymptomatic Hwc plants along with four different suspected insect vectors were analysed by double antibody sandwich‐enzyme linked immunosorbent assay (DAS‐ELISA), dot blot hybridisation and RT‐PCR. CNRMV was detected in 57% of the wild cherry samples, two aphid species Astegopteryx bambusae and Tinocalloides montanus, and in a delphacid of Bambusiphaga sp. Complete coat protein (CP) gene of CNRMV was sequenced from two randomly selected samples. The isolates characterised from Hwc shared 99% similarity to the already characterised isolates of CNRMV from India, suggesting a conserved nature of the CP gene. This study represents the first report of CNRMV infection in Himalayan wild cherry and its possible insect vectors.